The Education and Training Program on Hospital Management Information System for Healthcare Workers in the Surakarta Region - Maulindar, Joni; Sutrisna, EM; Studiviani Dwi Binuko, Raafika (International Journal of Community Service Implementation, 2024)
Healthcare workers in the Surakarta region still face challenges in understanding and operating the Hospital Management Information System, which impacts work efficiency and service quality. This program aims to enhance the competencies of healthcare workers through education and training based on lectures, simulations, and evaluations via pre-test and post-test assessments. The community service method included delivering lecture materials, practical training with case simulations, and evaluating participants' comprehension improvements. The results show that the average pre-test score was 58, while the post-test score increased significantly to 85, reflecting a 46.6% improvement. Understanding of Hospital Management Information System concepts improved from 62 to 85, mastery of basic features from 58 to 88, and data analysis skills from 54 to 82. A total of 95% of participants found the training relevant and effective, while 89% expressed confidence in using Hospital Management Information System. Feedback from participants and hospitals indicated that the training successfully contributed to administrative efficiency and prepared healthcare workers for digital transformation.